Doubling Down on Double Standards: The Politics of Solidarity in the Externalization Society - Lessenich, Stephan (Journal of Political Sociology, 2023)
This article takes as its starting point the claim that the sociopolitical common-sense view according to which the European welfare state is an arrangement of institutionalized solidarity draws its support from a one-sided scientific-political narrative. My reflections boil down to the claim that this, as it were, semiofficial narrative is completely right—and yet at the same time completely wrong. Its ambiguity is characteristic of a politics of solidarity that will be defined in greater detail here. This ambiguity is by no means exhausted in the discursive dimension, but has a variety of material implications, namely, in the shape of structures of social closure whose historical dynamics have proven to be remarkably stable but are conspicuously absent from the self-description of the European welfare state. However, since the welfare state in its European manifestation, as an arrangement of solidarity, is invariably at the same time invested with a pronounced moral meaning by its proponents as well as its critics, the politics of the welfare state is a prototypical example of the social double standard that can be regarded as the cultural signature of what I call the externalization society.